2013
DOI: 10.1057/hs.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

End-user support for primary care electronic medical records: a qualitative case study of users’ needs, expectations, and realities

Abstract: Support is considered an important factor for realizing the benefits of health information technology (HIT) but there is a dearth of research on the topic of support, especially in primary care. We conducted a qualitative multiple case study of 4 family health teams (FHTs) and one family health organization (FHO) in Ontario, Canada in an attempt to gain insight into users' expectations and needs, and the realities of end-user support for primary care electronic medical records (EMRs). Data were collected by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Without strong support to help clinicians and other system users to effectively adapt a new EHR, distrust, frustration, and slow adoption can result. 4 In an article by Boonstra and Broekhus, physicians perceived a need for proper support and were reluctant to use the EHR without it. 5 Simon et al, found that two-thirds of physicians indicated a lack of support as a barrier to them adopting EHRs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Without strong support to help clinicians and other system users to effectively adapt a new EHR, distrust, frustration, and slow adoption can result. 4 In an article by Boonstra and Broekhus, physicians perceived a need for proper support and were reluctant to use the EHR without it. 5 Simon et al, found that two-thirds of physicians indicated a lack of support as a barrier to them adopting EHRs.…”
mentioning
confidence: 99%
“…7 A common theme in the literature emphasizes the need for providing on-site support during implementation and is seen as a critical factor to effective adoption. 4,5,[7][8][9][10][11][12] Using the model for improvement, endorsed by the Institute for Healthcare Improvement as a framework, this case report will describe the activities that follow the planning, doing, studying, and acting of providing on-site support to clinicians and other system end-users at Vanderbilt University Medical Center (VUMC) during a recent EHR implementation. Activities and processes deemed as effective during the first 3 weeks of implementation will be shared along with challenges and lessons learned.…”
mentioning
confidence: 99%
“…In the present review Net Benefits refer to barriers and facilitators of ICF use in EHRs. The HOT-fit framework builds upon knowledge based on health and information sciences [27] and has been recommended and recently used for evaluation of health information systems [28][29][30][31][32]. Information relevant to the use of the ICF in an EHR system was extracted and categorized according to the HOT-fit framework using an Excel® spreadsheet.…”
Section: Information Extraction and Descriptive Synthesis Of Resultsmentioning
confidence: 99%
“…In particular, the present study assesses the usability and technological aspects of the ODK Scan supported by the perspective of the field workers in relation to their work settings. However, it is also noted that in the developing country context, a prerequisite to the success of mHealth interventions is the consideration of developers and implementers about the field workers' expectations, needs and work settings [29,30]. Moreover, a gap between the work practices and use of the new technologies is attributed by the poor implementation design of the technology-based interventions [31].…”
Section: Discussionmentioning
confidence: 99%